The Effect of Different Topical Agents (Silver Sulfadiazine, Povidone-Iodine, and Sodium Chloride 0.9%) on Burn Injuries in Rats. (28th September 2014) - Yüksel, Emir Burak; Yıldırım, Alpagan Mustafa; Bal, Ali; Kuloglu, Tuncay
Abstract : It was aimed to comparatively evaluate the effects of dressing methods with silver sulfadiazine, povidone-iodine, and saline which have a common use in routine practices for burn injuries. Twenty-eight Sprague Dawley adult female rats were used in this study. All the rats were divided into 4 groups: the control group, the povidone-iodine group, the saline group, and the silver sulfadiazine group. On each rat, a second degree burn which covered less than 10% of the body surface area was created under general anesthesia by a metal comb including four probes with 2 × 1 cm area. The control group did not have any treatment during the experiment. Povidone-iodine, saline, and silver sulfadiazine administrations were performed under ether anesthesia every day. On 0, 7th, 14th, and 21st days of the study, tissue samples were taken for histological analyses. The sections taken from the paraffin blocks were stained and avidin-biotin-peroxidase method was used for collagen immune-reactivity. In the light microscope analyses, number of inflammatory cells, vascularization, fibroblast proliferation, collagen formation and epithelialization were evaluated histologically in all groups and analysed statistically. The agents that we used for injury healing in the treatment groups did not show any significant better results in comparison with the control group. In conclusion, further studies with the use of sodium chloride, silver sulfadiazine, and povidone-iodine by creating deeper and/or larger burn injury models are needed in order to accept these agents in routine treatment.